350 ORANG ASLI INVOLVED IN USM ORAL CANCER AWARENESS PROGRAMME - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 24 November 2016 350 Semai Tribe Orang Asli comprising children, youth, and adults are expected to be involved in the Oral Cancer Awareness Programme, organised by the Advanced Medical and Dental Institute (AMDI), Universiti Sains Malaysia. This programme is funded by the Industry and Community Network Division (BJIM), Universiti Sains Malaysia (USM).